2008
DOI: 10.1007/s11293-008-9158-2
|View full text |Cite
|
Sign up to set email alerts
|

A Short-Run Crude Oil Price Forecast Model with Ratchet Effect

Abstract: Crude oil prices, Crude oil inventory, Crude oil excess production capacity, Duesenberry ratchet effect, Q00 Agriculture and Natural Resources,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Frequently, the identified model is rather simple and comprises either ADL(0,1) or ADL(1,1) formulations. The keep-it-simple approach to modeling, coupled to avoiding overparameterization risks, reduces the Ye et al, 2009 complexity of the model. The evaluation of a,b,c parameters in Eqn (25.3) is carried out by a linear regression procedure (e.g., multidimensional unconstrained optimization) that minimizes the sum of squared errors between real quotations and model values.…”
Section: Ems Of Raw Materials and (By)productsmentioning
confidence: 99%
“…Frequently, the identified model is rather simple and comprises either ADL(0,1) or ADL(1,1) formulations. The keep-it-simple approach to modeling, coupled to avoiding overparameterization risks, reduces the Ye et al, 2009 complexity of the model. The evaluation of a,b,c parameters in Eqn (25.3) is carried out by a linear regression procedure (e.g., multidimensional unconstrained optimization) that minimizes the sum of squared errors between real quotations and model values.…”
Section: Ems Of Raw Materials and (By)productsmentioning
confidence: 99%
“…To explain and predict changes in crude oil prices firstly need to understand the behavior of crude oil prices itself (Michael (2009) [5]; Kendix (2010) [6]; Leder (2008) [7]). Jose (2002) [8] analysis results on the price of crude oil using Hurst multidimensional showed that the crude oil market is a highly complex process of interaction at different time scale, long-term memory mechanism to influence the evolution of oil prices.…”
Section: Quanmentioning
confidence: 99%
“…(Chaudhuri K (2001) [14]; Smith, Grimm (2003) [15]; Michael Ye, John Zyren, Carol Joyce Blumberg, Joanne Shore (2009) [16]; Watkins, G.C. and Plourde (1994) [17]).…”
Section: Quanmentioning
confidence: 99%
“…Cuaresma et al [88], using a simple unobserved components model, showed that explicitly modelling asymmetric cycles on crude oil prices improves the forecast ability of univariate time series models of the oil price. Ye et al [89] predicted crude oil prices from 1992 through early 2004 by using OECD's relative inventories and OPEC's excess production capacity improving forecasts for the post-Gulf War I time period over models without the ratchet mechanism. Cheong [90] investigated the timevarying volatility of two major crude oil markets, the West Texas Intermediate (WTI) and the Europe Brent, with a flexible autoregressive conditional heteroskedasticity (ARCH) model to take into account the stylized volatility facts such as clustering volatility, asymmetric news impact, and long memory volatility.…”
Section: Introductionmentioning
confidence: 99%